Concept Analysis of Rigor in Nursing Education. (July 2019) - Gerdes, Michele A.
The term rigor appears in nursing education literature, but the definitions are inconsistent. Likewise, there is variation in the implementation of rigor in nursing curricula and courses. Nurse educators need a clear and shared understanding of rigor to prepare graduates to use critical thinking. The purpose of this concept analysis is to gain understanding of the meaning of rigor in nursing education so that educators can establish a standardized definition, which will contribute to consistency of its application in learning environments with uniform criteria for curricula evaluation.